1998
DOI: 10.1108/00251749810204124
|View full text |Cite
|
Sign up to set email alerts
|

Organizational performance and environmental consciousness: an empirical study

Abstract: This study investigates the relationship between environmental strategy and company performance using samples from a nationwide survey. The companies were classified into two groups; environmentally conscious and nonenvironmental companies. Environmental companies reported better performance scores and also are more inclined to incorporate various performance improvement strategies and techniques into their operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
65
1
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 16 publications
3
65
1
2
Order By: Relevance
“…A favorable CSR towards environment increasing FP and NFP of firms supports past findings (Ahmed et al, 1998;Alvarez et al, 2001). Environmentally compatible products, processes and management systems enhance profitability either through revenue gains or through cost savings.…”
Section: Csr Towards Environment and Firm Performancesupporting
confidence: 77%
See 2 more Smart Citations
“…A favorable CSR towards environment increasing FP and NFP of firms supports past findings (Ahmed et al, 1998;Alvarez et al, 2001). Environmentally compatible products, processes and management systems enhance profitability either through revenue gains or through cost savings.…”
Section: Csr Towards Environment and Firm Performancesupporting
confidence: 77%
“…Evidence suggests proactive environment management enhances firm's market value (Klassen and Mc Laughlin, 1996), reputation, and FP (Alvarez et al, 2001;Miles and Covin, 2000). The impact of firms' proactive environmental practices on market share, profitability, and return on investment is better in environmentally conscious companies compared to not-soconscious companies (Ahmed et al, 1998). Hence,…”
Section: Csr Towards Investors and Firm Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The cost issue probably becomes dominant for these companies over classic CSR issues. In other words, the smaller the family companies become, the more they focus on the economic bottom line to survive in the market (Ahmed et al 1998;Graafland et al 2003). A study by Uhlaner et al (2004) found that family businesses have stronger links to employees, customers, and suppliers.…”
Section: Theoretical Insightsmentioning
confidence: 99%
“…However, the sample of the study was more focused on small companies with less than 50 employees. This might explain why only primary stakeholders are emphasised by family businesses because if we follow the argumentation of Ahmed et al (1998) and Graafland et al (2003) these stakeholders are most important to survive in the market.…”
Section: Theoretical Insightsmentioning
confidence: 99%